2022
DOI: 10.1186/s41687-022-00423-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (HRQoL) from HIV patients’ perspective: comparison of patient-reported outcome (PRO) measures among people living with hiv (PLWH) and other chronic clinical conditions

Abstract: Background People living with HIV (PLWH) are generally known to suffer from a lower quality of life compared to the one of general population, but still very few is known about the self-perception of quality of life when comparing HIV to non-communicable diseases. We performed a comprehensive assessment of patient’s reported outcomes measures (PROMs) among PLWH and patients affected by other chronic conditions (OC) such as diabetes mellitus type 1, rheumatoid arthritis, breast cancer in hormona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The demographic characteristics of the overall ART population reported a male predominance and a mean age of around 49 years, which is in line with other Italian real-world studies on HIV [1,23]. Hypertension and dyslipidemia were among the most frequent comorbidities detected; a French study also observed these two conditions to be highly prevalent in PLWH [24].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The demographic characteristics of the overall ART population reported a male predominance and a mean age of around 49 years, which is in line with other Italian real-world studies on HIV [1,23]. Hypertension and dyslipidemia were among the most frequent comorbidities detected; a French study also observed these two conditions to be highly prevalent in PLWH [24].…”
Section: Discussionsupporting
confidence: 86%
“…The development and introduction of antiretroviral therapies (ART) and then the availability of combination ART in the clinical practice has dramatically changed the course of human immunodeficiency virus (HIV) infection from an acute to a chronic disease [1]. Nowadays, life expectancy for people living with HIV (PLWH) is up to that of the general population in those patients who receive a prompt diagnosis and early treatment and achieve adequate viral-load suppression [2].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of a generic PROM is that it enables researchers to compare the health outcomes of people living with HIV and AIDS with those of other populations based on the same measurements [16]. However, unlike generic PROMs, HIV-specific PROMs do not have a significant ceiling and floor effect and do not overestimate health outcomes in people living with HIV and AIDS [17,18]. Furthermore, HIV-specific PROMs are more closely associated with HIV than are generic PROMs.…”
Section: Why Did This Systematic Review Only Include Hiv-specific Pro...mentioning
confidence: 99%
“…1,4 Though the survival is prolonged, still PLHIV continue to suffer from many physical problems including side effects of therapy like pain and fatigue, etc., mental health issues like depression and social issues like isolation. 5,6,7 All these things determine their health status and impact the quality of life (QOL) of PLHIV. 8 As per the World Health Organization (WHO), 'Quality of Life is an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns'.…”
Section: Introductionmentioning
confidence: 99%